ChemInform Abstract: Anionic Access to Silylated and Germylated Binuclear Heterocycles. Issue 6 (23rd January 2015) - Boddaert, Thomas; Francois, Cyril; Mistico, Laetitia; Querolle, Olivier; Meerpoel, Lieven; Angibaud, Patrick; Durandetti, Muriel; Maddaluno, Jacques
Abstract The sila‐Matteson rearrangement is studied to allow access to silicon‐containing binuclear heterocycles.